Neural correlates of apathy in late-life depression: a pilot [(18)F]FDDNP positron emission tomography study - Eyre, Harris A. (Psychogeriatrics, 2017)
BACKGROUND: Neurotoxicity associated with amyloid and tau protein aggregation could represent a pathophysiological cascade that, along with vascular compromise, may predispose individuals to late-life depression (LLD). In LLD, apathy is common, leads to worsening of functioning, and responds poorly to antidepressant treatment. Better understanding of the pathophysiological mechanisms of apathy in LLD would facilitate development of more effective diagnostic and treatment approaches. In this cross-sectional pilot study, we performed positron emission tomography scans after injection of 2-(1-{6-[(2-[(18)F]fluoroethyl)(methyl)-amino]-2-naphthyl}ethylidene) malononitrile ([(18)F]FDDNP), an in vivo amyloid and tau neuroimaging study, in patients with LLD to explore neural correlates of apathy. METHODS: Sixteen depressed elderly volunteers received clinical assessments and [(18)F]FDDNP positron emission tomography scans. The cross-sectional relationship of [(18)F]FDDNP binding levels with depression (Hamilton Depression Rating Scale) and apathy (Apathy Evaluation Scale) were studied using Spearman's correlation analyses because of the relatively small sample size. Age, sex, and years of education were partialed out. Significance levels were set at P ≤ 0.05. RESULTS: [(18)F]FDDNP binding in the anterior cingulate cortex was negatively associated with the Apathy Evaluation Scale total (r = -0.62, P = 0.02; where low Apathy Evaluation Scale score equals greater severity of apathy). This suggests that apathy in LLD is associated with higher amyloid and/or tau levels in the anterior cingulate cortex. None of the regional [(18)F]FDDNP binding levels was significantly associated with the Hamilton Depression Rating Scale total. CONCLUSION: This pilot study suggests that increased apathy in subjects with LLD may be associated with greater amyloid and/or tau burden in certain brain regions. Future studies in larger samples would elucidate the generalizability of these results, which eventually could lead to improved diagnostic and treatment methods in LLD.